Pelanggaran Asas Itikad Baik dalam Penggunaan Merek Tanpa Seizin Pemilik Hak Merek PB Oleh PT Garuda Tasco - Tambunan, Joseph Armando (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The implementation of registration in Indonesia must comply with the provisions of Law Number 20 of 2016 concerning Marks and Geographical Indications (hereinafter referred to as the MIG Law). In the MIG Law, it is stated that registration must be based on the principle of good faith. In an effort to provide protection to registered trademark holders for trademark plagiarism by other parties. Violation of the registered trademark rights holder will of course cause harm to the trademark rights holder. This research method is a type of normative juridical research, namely examining phenomena that occur in accordance with applicable laws and regulations. The nature of this research is descriptive, namely research that describes, examines, and explains and analyzes a legal regulation.